Escitalopram add-on in stable Schizophrenia with subsyndromal depression - Nischal, Anil; Singh, Pooja; Agarwal, Manu; Nischal, Anuradha; Gupta, Bandna; Tripathi, Adarsh (International Journal of Advances in Medicine, 2020)
Background: Significant proportion of the patients of schizophrenia suffer from subsyndromal symptomatic depressive symptoms (SSD) which not only add to the burden of disease but also to the already pre-existing challenges of living with this serious mental illness. Many psychiatrists prescribe antidepressants to patients with schizophrenia who have subsyndromal symptomatic depressive symptoms but data regarding SSD in schizophrenia is meagre. Aim was to study the effect of addition of Escitalopram on psychopathology, cognition and functioning in patients with stable schizophrenia having subsyndromal depressive symptoms and to compare these parameters with patients treated with antipsychotics alone. Methods: The study was a prospective, 8-week randomized double-blind placebo-controlled trial. Seventy four patients who fulfilled the diagnostic criteria of Schizophrenia on the basis of the ICD10-DCR, adjudged to be stable clinically and not requiring any increase in dose of antipsychotic medication over the last eight weeks were recruited into the study. The patients randomly received either Antipsychotics with add-on Escitalopram (10 mg/day) or Antipsychotics with placebo for 8 weeks. The patients were assessed using the HAM-D, CDRS, PANSS, SCoRS, SOFAS and CGI scores at the end of 8 weeks. Patients were also assessed for adverse events at baseline, week 4 and week 8. Results: A total of sixty-six patients who completed the study were analyzed. The HAM-D, CDRS and PANSS score showed significantly better cognition and functioning in the patients of add-on Escitalopram group when compared with the placebo group. There was no significant difference between the two groups in terms of observed side effects. Conclusions: Escitalopram addition to the standard anti-psychotic treatment of schizophrenia, in patients having subsyndromal depressive symptoms, results in better cognition and improved functioning.